Teaching target language culture: the learning of the target culture is an essential part of learning a foreign language - Batres González, Jullianny Bayarone; Mercado Tiznado, Karen Eloisa; Ramírez Hernández, Maira Teresa (2024)
Nowadays, the English language is spread around the world. Many experts agree that teaching language is not just the knowledge of phonology, morphology, syntax, etc.; it is in the context where students can learn the target language. This paper aims at explaining to teachers as well as students why and how culture should be taught. Moreover, the paper explains the interrelationship between language and culture by stating that they are inseparable. Furthermore, it gives an alternative by taking into consideration the possibility of applying the Intercultural Approach (IA), which is a choice for students of English as a Foreign Language (EFL) to get familiar with the Target Language Culture (TLC). At the end of this paper, the reader will find the current situation of teaching culture in the Foreign Language Department (FLD) of the University of El Salvador (UES). The main objective of this paper is to propose the teaching of target language culture since it helps students to feel empathy and respect towards other peoples’ customs, behaviors, and lifestyles. Also, culture motivates students to learn the language since they become critical and aware of their own culture and; at the same time, they improve their four macroskills too. Finally and most important is that applying culture in language teaching helps students to improve their communicative competence.